Inclusive sensory ethnography: Studying new media and neurodiversity in everyday life. (October 2018) - Alper, Meryl
Media and communication studies has recently begun to ethnographically explore the sensory dimensions of how individuals experience and perceive technology. This turn toward the sensorial has centered primarily on the five "external" senses (sight, sound, touch, smell, and taste) and less so on "internal" vestibular and proprioceptive systems that concern bodily spatial positioning. I propose inclusive sensory ethnography to account for greater neurodiversity in how humans process sensory input, as well as a fuller range of multi-sensory encounters with new media. I ground this conceptualization in a qualitative study of young children on the autism spectrum with difficulties processing sensory information and their social engagements with print, screen, and interactive media. Inclusive sensory ethnography reveals novel understandings of how the internal senses shape and are shaped by mediated relationships, practices, and intimacies. I discuss further implications for how disability and inclusive sensory ethnography can enrich the study of everyday technology use.